Harnessing Nanotechnology for Environmental Sustainability: Applications, Challenges, and Future Perspectives - Areeba Sagheer; Muhammad Iqbal; Duaa Sagheer; Areesha Sagheer; Muhammad Madnee; Hussain Ahmed Makki; Intazar Ali; Nugraha Akbar Nurrochmat (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2026)
Background: Nanotechnology has emerged as a transformative and rapidly advancing field with significant potential to address pressing environmental challenges. Owing to the unique properties of nanoparticles, particularly their high surface area-to-volume ratio and enhanced reactivity, nanotechnology offers innovative solutions across multiple environmental sectors. Aim: This review aims to explore the applications, advantages, challenges, and future perspectives of nanotechnology in promoting environmental sustainability. Methods: A comprehensive literature review approach was employed to examine the role of nanotechnology in key areas, including climate change mitigation, wastewater treatment, sustainable agriculture, food quality enhancement, and civil engineering. Conclusion: Nanotechnology provides cost-effective, efficient, and sustainable solutions for reducing environmental pollutants, improving resource management, and enhancing ecosystem resilience. However, concerns regarding environmental toxicity, long-term impacts, and regulatory challenges highlight the need for further research, risk assessment, and the development of robust regulatory frameworks to ensure its safe and widespread implementation.